A CRITICAL DISCOURSE ANALYSIS OF MENTAL HEALTH AWARENESS IN INSTAGRAM CAPTIONS - Murni Amalia (Universitas Negeri Islam Sumatera Utara, 2026)
Mental health awareness has increasingly been communicated through social media platforms, particularly Instagram, which serves as a space for public education and advocacy. This study aims to examine how mental health awareness is discursively constructed in Instagram captions published by a mental health organization. Employing a qualitative approach, the research applies Critical Discourse Analysis (CDA) based on Teun A. van Dijk’s framework to explore the underlying meanings and communicative strategies embedded within the texts. The data consist of six English-language Instagram captions posted by the account @mmha_1968, selected through purposive sampling based on their relevance to mental health awareness and public education. The analysis focuses on thematic, semantic, lexical, and rhetorical structures to reveal how mental health issues are represented and framed. The findings indicate that the captions consistently construct mental health as a shared social concern rather than an individual weakness. Through empathetic lexical choices, inclusive pronouns, and rhetorical strategies such as repetition and reflective questioning, the discourse promotes understanding, reduces stigma, and encourages collective responsibility. The study concludes that Instagram captions function not only as informational texts but also as powerful discursive tools that shape public perceptions of mental health. This research contributes to discourse studies by demonstrating the role of digital media in constructing mental health awareness and highlighting the relevance of CDA for analyzing contemporary social media discourse.